National Identity in the Digital Age: Challenges and Opportunities for Strengthening National Solidarity - Saiman Saiman (Sean Institute, 2025)
This research aims to analyze the dynamics of national identity in the digital era and explore the challenges and opportunities for strengthening national solidarity. Developments in information and communication technology have transformed the way people interact, form opinions, and express their identities, giving rise to new challenges related to social cohesion and national awareness. This research method uses a qualitative approach with literature review techniques. The results indicate that the digital era brings challenges and opportunities for strengthening national identity and social solidarity. The main challenges include the influx of foreign cultures, hoaxes and information polarization, individualistic attitudes, and the dominance of foreign languages, which have the potential to weaken traditional values and social cohesion. On the other hand, digital media opens up opportunities for cultural promotion, character education, creative expression, social mobilization, digital literacy, and campaigns to promote local products, which can strengthen national awareness and emotional attachment to national identity. Strategies for strengthening identity and solidarity require the wise use of digital media, cross-sector collaboration, and adaptive education that instills the values of Pancasila and the Indonesian archipelago perspective, so that the younger generation can internalize national values creatively and participatoryly.